Dispersive double bent crystal monochromators Si(111) + Si(311) and Si(111) + Si(400) with a strongly asymmetric diffraction geometry of the analyzer for powder diffractometry. (September 2019) - Mikula, P.; Vrana, M.; Saroun, J.; Stammers, J.; Em, V.
Abstract : In this paper, some results of neutron diffraction properties of the dispersive double-crystal Si(111) + Si(311) and Si(111) + Si(400) monochromator settings containing two bent perfect crystals but with the second one – analyzer in the strongly asymmetric diffraction geometry, are presented. For the sake of possible applications, both double crystal settings were tested in the orientation of the second crystal for the output beam compression geometry. Powder diffraction test was carried out on a α -Fe(211) pin of the diameter of 2 mm. Contrary to the Si(111) + Si(400) setting, an excellent resolution represented by full width at half maximum in the ( Δd/d )-scale was obtained for the Si(111) + Si(311) double crystal monochromator in the parallel as well as in the antiparallel diffraction geometry.